2016
DOI: 10.1038/srep26524
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA CASC2 functions as a competing endogenous RNA by sponging miR-18a in colorectal cancer

Abstract: Recent evidence highlights the crucial regulatory roles of long noncoding RNAs (lncRNA) in tumor biology. In colorectal cancer (CRC), the expression of several lncRNAs is dysregulated and play essential roles in CRC tumorigenesis. However, the potential biological roles and regulatory mechanisms of the novel human lncRNA, CASC2 (cancer susceptibility candidate 2), in tumor biology are poorly understood. In this study, CASC2 expression was significantly decreased in CRC tissues and CRC cell lines, and decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 42 publications
(45 reference statements)
6
118
0
Order By: Relevance
“…An example of this type of regulation was exemplified by cancer susceptibility candidate 2 (CASC2), whose decreased expression is in part due to its oncogenic effects on the expression and activity of miR-18a in colorectal cancer [32]. Similar studies have revealed that long noncoding RNA activated by TGF-β (lncRNA-ATB) upregulates ZEB1 and ZEB2 expression by competitively binding the miR-200 family, which induces epithelial-mesenchymal transition (EMT) and invasion in hepatocellular carcinoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…An example of this type of regulation was exemplified by cancer susceptibility candidate 2 (CASC2), whose decreased expression is in part due to its oncogenic effects on the expression and activity of miR-18a in colorectal cancer [32]. Similar studies have revealed that long noncoding RNA activated by TGF-β (lncRNA-ATB) upregulates ZEB1 and ZEB2 expression by competitively binding the miR-200 family, which induces epithelial-mesenchymal transition (EMT) and invasion in hepatocellular carcinoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ceRNA regulation mechanism has also been reported to play an important role in cell proliferation of esophageal cancer and CRC. [34,35] ZNF148 is over-expressed in CRC, and it inhibits cell proliferation in CRC cells. The underlying mechanism is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…72 Huang et al 62 recently conducted a study that suggests that CASC2 expression was not only visibly reduced in CRC cell lines and CRC tissues but also more obviously decreased in patients with advanced CRC.…”
Section: Cancer Susceptibility Candidatementioning
confidence: 99%